A stump appendicitis in a child: a case report - Jemaï Radhia; Sahli Sondes; Fitouri Fatma; Gasmi Manef; Hamzaoui Mourad (BMC, 2009)
Abstract Background Stump appendicitis is a delayed complication of appendectomy. It is rare and few cases reported in the paediatric literature. The authors report on another case in a child and focus on the diagnostic peculiarities of this entity. Case A 9-year-old boy with previous history of open appendectomy was admitted for a right lower quadrant pain with bilious vomiting and fever. Physical examination demonstrated tenderness in the right lower quadrant and guarding over the appendectomy scar. The white blood cell count was 23.500 cells/mm3. Plain abdominal radiograph and ultrasonography revealed fecalith localized in the right iliac fossa. The diagnosis of stump appendicitis was advocated and confirmed at laparotomy. A gangrenous and perforated appendiceal stump was found and completely removed. The post-operative course was uneventful after 18 months follow-up period. Conclusion Stump appendicitis is rare and should be considered in any patient with right lower quadrant pain even if there is a history of appendectomy. Complete removal of the appendix is the only mean to prevent the occurrence of this complication.